Social enterprises and their ecosystems in Europe (Publications Office of the European Union, 2016)
Viewed as a small but growing part of the enterprise base, there is widespread acceptance of the contribution of social enterprise to national social and economic development. Rooted in a rich social economy tradition, the term 'social enterprise' first came to prominence in Irish policy discourse in the 1990s and was typically viewed as a response to community service provision and work integration. This association with service provision and labour market integration has persisted in national discourse, as reflected in the Action Plan for Jobs (2012) and the subsequent Programme for Government 2011-16 which contains a promise to promote the development of the sector. The most recent national operational definition of a social enterprise defines it as 'an enterprise that trades for a social/societal purpose, where at least part of its income is earned from its trading activity, is separate from government, and where the surplus is primarily re-invested in the social objective'. Four main types of (non-mutually exclusive) social enterprise have been identified: those with commercial opportunities that are established to create a social return; those creating employment opportunities for marginalised groups; economic and community development organisations; and those that deliver services. The eco-system for Irish social enterprises has been enriched in the last decade through the emergence of national support networks, advocacy groups for the sector and increased access to social and micro-financial support mechanisms as a result of national, EU and philanthropic support. New opportunities for social enterprises are presented in the recent transposition of two EU Directives into Irish law in 2016. The two Regulations cover public procurement in the public service and the utilities sector, and include provisions allowing for discretion to divide public contracts into lots and for particular contracts to be reserved for social enterprises under certain conditions. However despite these emerging potential opportunities the future development of the sector is also constrained by a variety of internal sectoral factors including: the need for improved business and governance skills; the need for increased capacity to engage in the future competitive tendering process for public sector contracts; and the development and implementation of appropriate social impact and performance measurement systems. While Irish law does not currently provide for a legal form specifically tailored for use by social enterprises, Irish social enterprises typically adopt the legal form of a Company Limited by Guarantee (CLG) with charitable status and are estimated to employ between 25 000 and 33 000 people in over 1 400 social enterprises, with a total income of around EUR 1.4 billion. However there are considerable gaps in our knowledge about Irish social enterprises, including the scale, social impact, and overall contribution of the sector to the national economy and society in general. Addressing these gaps is an important next step in improving our understanding of social enterprise and in assessing its significance, value and true potential.
10.2767/755862
Keywords: Amtsdruckschrift; Graue Literatur; Sozialwirtschaft; Irland; social policy; social economy; social impact; European undertaking; financial aid; entrepreneurship; investment; cartography; research and development; financing; social development; labour market; microfinance; directive (EU); governance; public contract; Ireland; report